Social Networks and Household Dietary Diversity, Evidence from Smallholder Farmers in Kenya. - Mbugua, M.; Nzuma, J.; Muange, Elijah; Njuguna, M. (My University, 2018)
An important driver of household dietary diversity is nutrition knowledge which can be improved through access to nutrition information. However, in many rural areas, formal flow of nutrition information is limited, and social networks could play an important role as an informal source of such information. This paper evaluates effects of social network on household dietary diversity in Kenya. Cross sectional data collected from 198 farmers using multi stage sampling technique, was analysed using a Poisson regression model. The results show that the average household dietary diversity of an individual’s network members has a positive effect on the dietary diversity of the individual. The effects are more when the network includes at least a strong tie. Household size and farm size also have a positive effect on household dietary diversity. These results imply that farmers’ social networks could be used as a complementary tool for effective delivery of nutrition education which targets to enhance nutritional quality. Acknowledegment: Acknowledgements The field research of this paper was jointly carried out by the University of Nairobi, University of Gottingen and Africa Harvest Biotech Foundation International. The authors warmly acknowledge the Germany Federal Ministry of Food and Agriculture for funding this study through Agriculture and Dietary Diversity in Africa (ADDA) project (grant number ADDA-UGOE/UoN: 2813FSNU01) . Last but not list, our gratitude goes to Theda Godeke (University of Gottingen) for her support and guidance through the field research.